Zum Ortsnamen Artern - Bichlmeier, Harald (Namenkundliche Informationen, 2024)
The Thuringian place name Artern has so far found two explanations, one (pre-)Proto-Germanic and one German. The comparison of the two etymologies, which seem to have existed side-by-side for decades without the proponents of either suggestion really having taken notice of the other one, shows that the (pre)-Germanic solution firstly does not make sense per se, and secondly, even if it did, it appears unnecessary for methodological reasons since a consistent explanation exists at a more recent linguistic level, namely an inner-German one. The name goes back to the dative plural (in locative use) of Old High German *artā̆rum, -un, -on ‘(among) the plowmen, farmers, settlers’ to the hapax legomenon Old High German artā̆ri ‘plowman, farmer, settler’.
Online veröffentlicht: 22. Mai 2025
Gesehen am 04.02.2026
Keywords: Ortsname; Artern